IMPLEMENTASI AKTIVITAS TERSTRUKTUR DALAM MENANAMKAN KARAKTER DISIPLIN SISWA GENERASI ALPHA DI SEKOLAH DASAR - Safitri; Dariyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the implementation of structured activities in fostering disciplinary character among Alpha Generation students in elementary schools. The method employed is a literature review with a qualitative descriptive approach. Research data were obtained from various secondary sources, including journal articles, conference proceedings, and scientific publications relevant to the research topic. Data collection was conducted through searching, selecting, and reviewing literature related to structured activities, character education, disciplinary character, the Alpha Generation, and elementary education. Data analysis was carried out by identifying, classifying, comparing, and synthesizing findings from previous studies to gain a comprehensive understanding of the topic under investigation. The results of the review indicate that consistently implemented structured activities, such as punctual attendance habits, morning literacy programs, classroom cleaning duties, and the enforcement of school regulations, are effective in developing students' disciplinary character. Furthermore, the successful implementation of structured activities is supported by teachers' roles as role models, a positive school culture, and parental involvement in reinforcing disciplinary habits. Therefore, structured activities can serve as an effective strategy for fostering disciplinary character among Alpha Generation students in elementary schools.